PENGARUH PEMBELAJARAN TEMA 5 WIRAUSAHA DENGAN MENGGUNAKAN PENDEKATAN DIFERENSIASI TERHADAP PRESTASI BELAJAR SISWA KELAS 6 SDN GUNUNG SARI II MAKASSAR - Wahyudi, Bambang; As, Husain.; Sulolipu, Andi Annisa (LPPM Institut Pendidikan Nusantara Global, 2023)
This study aims 1) To analyze and explain the application of the differentiation approach to learning activities on the 5th theme of entrepreneurship for students in class VI at SD Negeri Gunung Sari II Makassar, 2) To analyze and explain the effect of applying the differential approach to learning on the 5th theme of entrepreneurship on learning achievement class VI students at Gunung Sari II Public Elementary School, Makassar City. The population in this study were all grade VI of SD Negeri Gunung Sari II Makassar City. Based on the criteria that have been determined, the sample processed is 22 students in the entrepreneurship theme 5 learning activities. The collection of data used is observation, questionnaires and documentation. The data analysis technique used is the normality test and hypothesis testing technique which consists of descriptive statistical analysis and Inferential Statistical Data Analysis using SPSS software version.22. The results of this study indicate that 1) The average score obtained by students in the Class VI Pre Test at SD Negeri Gunung Sari II Makassar City is 69.91 which is in the medium category and the average score obtained by students in the Post Test Class V at SD Gunung Sari II State of Makassar City is 74.14 which is in the medium category. The results show that the use of a differentiation approach in learning activities on the theme of 5 entrepreneurship is effective for class VI students at SD Negeri Gunung Sari II Makassar City. 2) The results of data analysis obtained sig. 0.000. It turns out that the value of sig. 0.000 is smaller than the probability value of 0.05 or in other words the value of 0.05 > 0.000. So it can be concluded that there is a significant influence of the differentiation approach on learning activities on the 5th theme of entrepreneurship for class VI students at SD Negeri Gunung Sari II Makassar City.